2021
DOI: 10.1186/s13028-021-00587-x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of pre-weaning calf management in Norwegian dairy herds

Abstract: The knowledge on dairy calves’ needs with regards to milk feeding and social housing is expanding but to be able to make improvements, knowledge is needed on how calves are managed at present in Norway. The aim of this study was to describe selected milk-feeding practices and social housing procedures for young (pre-weaning) dairy calves in Norwegian herds. A short questionnaire was distributed to a random sample of 912 dairy producers. For each herd, we asked how much milk was fed to 3 week old dairy calves, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…There was a higher LBW in the RS group compared with the CR group. Our results are consistent with other findings [9,14,61] that the growth of suckling calves (RS) are higher than those artificially reared (CR), which probably received less valuable liquid nutrition [5,6,12,[62][63][64].…”
Section: Health and Reproductionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was a higher LBW in the RS group compared with the CR group. Our results are consistent with other findings [9,14,61] that the growth of suckling calves (RS) are higher than those artificially reared (CR), which probably received less valuable liquid nutrition [5,6,12,[62][63][64].…”
Section: Health and Reproductionsupporting
confidence: 92%
“…Calves born to cows under heat stress during the dry period are lighter at birth and have lower postnatal growth and passive immunity than calves born to cooled cows [28,38,39,41,[68][69][70][71]. These seasonal differences are likely caused by seasonal metabolic adaptations to enhance survival of the calf in different circumstances [64,66,67,72].…”
Section: Season Of Birth and Father's Lineage Factors (Sb F)mentioning
confidence: 99%
“…In conventional dairy farms, weaning occurs much earlier compared with when cow and calf are kept in extensive conditions or in cow–calf systems. Gradual weaning may be initiated as early as 4–6 weeks of life, but replacement dairy calves are commonly weaned off milk at 8–12 weeks of age (Drackley, 2008 ; Johnsen et al., 2021 ; Mahendran et al., 2022 ). Weaning strategies can be strictly age‐related but individual weaning schemes are also used, taking calf weight, concentrate intake or a combination hereof into account.…”
Section: Assessmentmentioning
confidence: 99%
“…When housed individually, calves must be able to see and touch other calves. In the EU there is a general increasing tendency of housing calves younger than 8 weeks in groups (Marcé et al., 2010 ; Johnsen et al., 2021 ; Mahendran et al., 2022 ), although figures from specific MSs indicate a different picture. For instance, a survey from Austria indicated that approximately 90% of farms housed calves individually after birth and 23% of these did so for longer than 6 weeks (Klein‐Jöbstl et al., 2015 ), a survey from the Czechia indicated that 97% of farms housed calves individually for a median of 8 weeks (Staněk et al., 2014 ), and a study from the UK indicated that the most prevalent initial type of housing used for newborn calves is individual housing (83/216, 38.4%), with pair housing used by 23.1% (50/216), and group housing of greater than 2 calves used by 35.6% (77/216) of the holdings (Mahendran et al., 2022 ).…”
Section: Assessmentmentioning
confidence: 99%
“…However, recent research suggests that calving facilities offer no opportunity for cows to seek seclusion during calving, which is a behavior observed in wild and domesticated ungulates before calving [7,10,11]. The discrepancy between current practice and recommendations places dairy cow welfare at risk and calls for further research and development in calving management systems [12]. A study has also observed that socially dominant cows are more likely to calve in an individual pen, while the presence of newly born calves to other cows may also influence calving behavior [13].…”
Section: Some Related Workmentioning
confidence: 99%